Introduktion: INDFØDTE FOLK I VERDEN OG I ANTROPOLOGIEN - Sjørslev, Inger (Tidsskriftet Antropologi, 1996)
Inger Sjørslev: Introduction: Indigenous peoples in the world and in anthropology The introduction presents the main themes of the articles, which derrive from a workshop held by The University of Copenhagen in cooperation with IWGIA, The International Workgroup for Indigenous Affairs, and the Ethnographic Department of the National Museum, Copenhagen. The workshop dealt with the situation of indigenous peoples in the globalized world and the State of current anthropological theory in relation to the indigenous issues, as this is presented by the „objects“ themselves within international fora, mainly the United Nations. Other themes are the concept of culture in relation to indigenous societies and anthropologists’ role in promoting the culture concept as a basis for dealing with indigenous rights, the questions of authenticity and reflexivity in relation to indigenous peoples’ culture, and the professional and ethical role of the anthropologist in dealing with indigenous issues.